2021
DOI: 10.1001/jamaneurol.2020.5257
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candidate Parkinson Disease Genes by Integrating Genome-Wide Association Study, Expression, and Epigenetic Data Sets

Abstract: Key Points Question What genes and genomic processes underlie risk of sporadic Parkinson disease? Findings This genetic association study integrated Parkinson disease genome-wide association study data and brain-derived gene regulation data using various complementary bioinformatic tools and identified 11 candidate genes with evidence of disease-associated regulatory changes. Coexpression and protein level analyses of these genes demonstrated a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(93 citation statements)
references
References 38 publications
8
72
0
Order By: Relevance
“…Among the 18 genes we identified, eight genes ( MMRN1 , CD38 , NUPL2 , GPNMB , RNF40 , VKORC1 , ZSWIM7 , and CENPV ) were significantly heritable in CMC dorsolateral prefrontal cortex and qualified for the TWAS analyses. According to the published results, seven of the above eight genes associated with PD risk at an FDR level of 0.05 (Supplementary Table 5 ), including two genes ( CD38 , and GPNMB ) with solid evidence for colocalization (PPH4 > 0.75) 27 . At the same time, numerous previously reported PD risk loci did not implicate in our TWAS.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Among the 18 genes we identified, eight genes ( MMRN1 , CD38 , NUPL2 , GPNMB , RNF40 , VKORC1 , ZSWIM7 , and CENPV ) were significantly heritable in CMC dorsolateral prefrontal cortex and qualified for the TWAS analyses. According to the published results, seven of the above eight genes associated with PD risk at an FDR level of 0.05 (Supplementary Table 5 ), including two genes ( CD38 , and GPNMB ) with solid evidence for colocalization (PPH4 > 0.75) 27 . At the same time, numerous previously reported PD risk loci did not implicate in our TWAS.…”
Section: Discussionmentioning
confidence: 98%
“…In parallel to ours, Kia and colleagues 27 conducted TWAS using expression weights from the CommonMind Consortium (CMC) dorsolateral prefrontal cortex to identify genes associated with PD. While considering the essential role of epigenetic features in predicting gene expression, our approach integrated the epigenetic information in the original TWAS to find gene–trait associations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the integration of genome-wide association studies, together with expression and epigenetic datasets, has recently suggested that gene regulation data may be used to identify candidate the genes and genomic processes underlying the risk of sporadic PD [ 42 ] ( Table 1 ). In particular, Kia and colleagues, using various complementary bioinformatics tools, integrated GWAS, the transcriptome-wide association study (TWAS) and methylation data and identified 11 candidate genes whose regulatory changes in expression, splicing or methylation are associated with the risk of PD.…”
Section: Parkinson’s Diseasementioning
confidence: 99%
“…Especially, GBA1 is well-known as a responsible gene for Gaucher disease, the most common lysosomal storage disorder. Moreover, the recent expansion of genetic, transcriptomic, and epigenetic studies in sporadic PD has nominated an increasing number of lysosomal pathway genes as a risk factor for PD (17)(18)(19). Endolysosomal dysfunctions are also frequently described in other neurodegenerative diseases such as Alzheimer's disease (AD), Huntington's disease (HD), frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS), all of which accompany neuronal accumulation of misfolded proteins (20,21).…”
Section: Introductionmentioning
confidence: 99%